1988
DOI: 10.1039/f19888401509
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Lewis acidity in layer aluminosilicates. Treatment with acetic acid

Abstract: The effect of exposure of Wyoming bentonite to glacial acetic acid has been studied by F.t.i.r., X.p.s, SEM and acidity measurements, in order to investigate the possibility of using such a non-aqueous technique as an alternative activation process. Treatment with glacial acetic acid, results in an overall increase in the concentration of acid sites. However, the number of Brarnsted sites is reduced, whereas the population of Lewis sites increases. This change is accompanied by the leaching out of A13+, but wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 0 publications
2
19
0
1
Order By: Relevance
“…Dealumination develops mesopores in the layers and contributes to high surface area. The protons exchanged for interlamellar ions and the leached hydrated alumina occupying the cation exchange sites result in enhanced acidity [6,[20][21][22][23][24][25]. It is now accepted that acid attack on the clay structure progresses inward from both the edge and the basal surface of the clay platelets, leaching cations, particularly Mg if present, from the octahedral sheet.…”
Section: Acid Treatment Of Claysmentioning
confidence: 99%
“…Dealumination develops mesopores in the layers and contributes to high surface area. The protons exchanged for interlamellar ions and the leached hydrated alumina occupying the cation exchange sites result in enhanced acidity [6,[20][21][22][23][24][25]. It is now accepted that acid attack on the clay structure progresses inward from both the edge and the basal surface of the clay platelets, leaching cations, particularly Mg if present, from the octahedral sheet.…”
Section: Acid Treatment Of Claysmentioning
confidence: 99%
“…Acid treatment, while being very important for mineral weathering and genesis (Jackson and Sherman, 1952;Eberl et al, 1993), often replaces exchangeable cations with H ions and releases Al and other cations from both tetrahedral and octahedral sites, but leaves the SiO 4 groups largely intact (Theocharis et al, 1988). It was reported that acid activation followed by thermal treatment increases the adsorption capacity to a good extent (Rodrigues, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…This is suggested to be due to the ability of the activating acid (HCl) to digest non-clay materials such as carbonates (absence of FTIR absorption band at 1430 cm -1 ) and partially leach out the cations located in the crystal structure of the clay during the acid activation process. Consequently, there is the delaminating of the clay that gives rise to increased surface area [16,17,33,34]. The increased surface area resulting from acid activation finds application in the refining of vegetable oils [33,34] and catalysis of esterification reactions [20,35].…”
Section: Egme-surface Area Of the Modified Claysmentioning
confidence: 99%
“…The net effect of this is a product with increased surface acidity, specific surface area and porosity, called acid activated clay mineral [16,17]. Acid activated clay minerals can occur naturally in the environment by the attack of acid on clay minerals as is the case with the acid mine drainage interacting with clay minerals [18,19].…”
mentioning
confidence: 99%